2018
DOI: 10.1038/s41398-018-0322-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex specific effects of pre-pubertal stress on hippocampal neurogenesis and behaviour

Abstract: Experience of traumatic events in childhood is linked to an elevated risk of developing psychiatric disorders in adulthood. The neurobiological mechanisms underlying this phenomenon are not fully understood. The limbic system, particularly the hippocampus, is significantly impacted by childhood trauma. In particular, it has been hypothesised that childhood stress may impact adult hippocampal neurogenesis (AHN) and related behaviours, conferring increased risk for later mental illness. Stress in utero can lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 80 publications
(95 reference statements)
5
21
0
Order By: Relevance
“…Specifically, the current study was consistent with prior brain imaging studies in victims of childhood abuse and related traumas (Baker et al, 2013;Bremner, 2002;Saleh et al, 2017). Previously, early childhood trauma has been reported to reduce volume of the insula (Baker et al, 2013), frontal lobe (Andersen et al, 2008), hippocampus (Brydges et al, 2018;Teicher et al, 2012), and anterior cingulate (Baker et al, 2013;Kasai et al, 2008;Kitayama et al, 2006) in adults. It has been hypothesized these morphological differences result from neuron loss, decreases in dendritic branching or spine density, or decreases neurogenesis with early childhood trauma (Baker et al, 2013) which are likely subjugated by an elevated stress response (i.e., increased/prolonged HPAA activation) within the developing brain (Twardosz and Lutzker, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, the current study was consistent with prior brain imaging studies in victims of childhood abuse and related traumas (Baker et al, 2013;Bremner, 2002;Saleh et al, 2017). Previously, early childhood trauma has been reported to reduce volume of the insula (Baker et al, 2013), frontal lobe (Andersen et al, 2008), hippocampus (Brydges et al, 2018;Teicher et al, 2012), and anterior cingulate (Baker et al, 2013;Kasai et al, 2008;Kitayama et al, 2006) in adults. It has been hypothesized these morphological differences result from neuron loss, decreases in dendritic branching or spine density, or decreases neurogenesis with early childhood trauma (Baker et al, 2013) which are likely subjugated by an elevated stress response (i.e., increased/prolonged HPAA activation) within the developing brain (Twardosz and Lutzker, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Traumatic events experienced during childhood can have deleterious consequences through adulthood such as hypo/hypersecretion of cortisol (Anda et al, 2006;Gunnar and Quevedo, 2007;Kalmakis et al, 2015;Yehuda, 2006), dysfunction of the hypothalamic-pituitary-adrenal axis (HPAA) (Yehuda, 2002), and impaired cognitive function (Lupien et al, 2009) potentially coalescing into psychiatric conditions such as PTSD or depression (Bremner et al, 2007;Gunnar and Quevedo, 2007). Neurobiological consequences of trauma exposure during childhood may also impair development within brain regions such as the prefrontal cortex (Lupien et al, 2009) and hippocampus (Bremner, 2003) which exert negative feedback on the HPAA (Bremner, 2003;Brydges et al, 2018). These adverse of effects of early childhood also appear in a graded manner, as greater number of trauma events are related to increased memory impairment, perceived stress, and greater difficulty controlling anger (Anda et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Proliferation, as measured by Ki67+ density, did not change, and there was no significant difference in immature neurons, as measured by DCX+ cell density. Additionally, within WT mice we observed fewer GFAP+ neurons in female mice relative to males, suggesting a major underlying sex difference in the level of postnatal neurogenesis, consistent with some prior findings (Juraska et al 1985; Falconer and Galea 2003; Brydges et al 2018; Yagi and Galea 2019). In a battery of behavioral tests, the most notable deficits were a male-specific deficiency in social recognition and impaired spatial learning that was strongest in the male cKO mice.…”
Section: Discussionsupporting
confidence: 91%
“…There are well-known sex-differences in the AVP and OXT systems, for example the expression of AVP and AVPR1a are typically higher in males, and the administration of AVP and AVPR1a antagonists can produce differing effects in males and females 102 . Previous research in our laboratory has demonstrated striking sex differences in response to our PPS paradigm, for example males display impaired fear conditioning and altered hippocampal neurogenesis, whereas females are unaffected 103 . Conversely, PPS females show greater alterations in the hypothalamic–pituitary–adrenal axis 104 .…”
Section: Discussionmentioning
confidence: 87%